Effect of bright light therapy on delayed sleep/wake cycle and reaction time of athletes participating in the Rio 2016 Olympic Games - Rosa, J. P. P.; Silva, A.; Rodrigues, D. F.; Simim, M. A.; Narciso, F. V.; Tufik, S.; Bichara, J. J.; Pereira, S. R. D.; Da Silva, S. C.; de Mello, M. T. (Chronobiology International, 2018)
This study investigated the effect of using an artificial bright light on the entrainment of the sleep/wake cycle as well as the reaction times of athletes before the Rio 2016 Olympic Games. A total of 22 athletes from the Brazilian Olympic Swimming Team were evaluated, with the aim of preparing them to compete at a time when they would normally be about to go to bed for the night. During the 8-day acclimatization period, their sleep/wake cycles were assessed by actigraphy, with all the athletes being treated with artificial light therapy for between 30 and 45 min (starting at day 3). In addition, other recommendations to improve sleep hygiene were made to the athletes. In order to assess reaction times, the Psychomotor Vigilance Test was performed before (day 1) and after (day 8) the bright light therapy. As a result of the intervention, the athletes slept later on the third (p = 0.01), seventh (p = 0.01) and eighth (p = 0.01) days after starting bright light therapy. Regarding reaction times, when tested in the morning the athletes showed improved average (p = 0.01) and minimum reaction time (p = 0.03) when comparing day 8 to day 1. When tested in the evening, they showed improved average (p = 0.04), minimum (p = 0.03) and maximum reaction time (p = 0.02) when comparing day 8 to day 1. Light therapy treatment delayed the sleep/wake cycles and improved reaction times of members of the swimming team. The use of bright light therapy was shown to be effective in modulating the sleep/wake cycles of athletes who had to perform in competitions that took place late at night.